Geothermal heat flux from measured temperature profiles in deep ice boreholes in Antarctica - P. Talalay; Y. Li; L. Augustin; G. D. Clow; J. Hong; E. Lefebvre; A. Markov; H. Motoyama; C. Ritz (The Cryosphere, 2020)
The temperature at the Antarctic Ice Sheet bed and the temperature gradient in subglacial rocks have been directly measured only a few times, although extensive thermodynamic modeling has been used to estimate the geothermal heat flux (GHF) under the ice sheet. During the last 5 decades, deep ice-core drilling projects at six sites – Byrd, WAIS Divide, Dome C, Kohnen, Dome F, and Vostok – have succeeded in reaching or nearly reaching the bed at inland locations in Antarctica. When temperature profiles in these boreholes and steady-state heat flow modeling are combined with estimates of vertical velocity, the heat flow at the ice-sheet base is translated to a geothermal heat flux of 57.9 ± 6.4 mW m−2 at Dome C, 78.9 ± 5.0 mW m−2 at Dome F, and 86.9 ± 16.6 mW m−2 at Kohnen, all higher than the predicted values at these sites. This warm base under the East Antarctic Ice Sheet (EAIS) could be caused by radiogenic heat effects or hydrothermal circulation not accounted for by the models. The GHF at the base of the ice sheet at Vostok has a negative value of −3.6 ± 5.3 mW m−2, indicating that water from Lake Vostok is freezing onto the ice-sheet base. Correlation analyses between modeled and measured depth–age scales at the EAIS sites indicate that all of them can be adequately approximated by a steady-state model. Horizontal velocities and their variation over ice-age cycles are much greater for the West Antarctic Ice Sheet than for the interior EAIS sites; a steady-state model cannot precisely describe the temperature distribution here. Even if the correlation factors for the best fitting age–depth curve are only moderate for the West Antarctic sites, the GHF values estimated here of 88.4 ± 7.6 mW m−2 at Byrd and 113.3 ± 16.9 mW m−2 at WAIS Divide can be used as references before more precise estimates are made on the subject.